EFEKTIFITAS PENGGUNAAN MEDIA E-POSTER TERHADAP PENGETAHUAN SIKAP DAN PERILAKU KONSUMSI TABLET TAMBAH DARAH (TTD) PADA REMAJA SISWI DI SMP NEGERI 1 JASINGA - Cinta Fitriany Tazqiyah; Witri Priawantiputri; Pusparini; Mulus Gumilar (Jurnal Gizi dan Dietetik, 2026)
Adolescence is an age that is vulnerable to nutritional problems due to an imbalance in nutritional intake and nutritional needs. One of the nutritional problems that often occurs in adolescence is a lack of micronutrients, one of which is anemia. Data from the Indonesian Ministry of Health from 2013 to 2018 shows that the increase in anemia in adolescents aged 15-24 years increased from 18.4% to 34%. Therefore, education on anemia and iron tablet consumption in adolescent girls is needed. This study aims to determine the effectiveness of e-poster media on increasing knowledge, attitudes and behavior of iron tablet consumption with a Quasi Experimental research design with a controlled group pre-post test. The sample consisted of 48 seventh-grade students of SMP Negeri 1 Jasinga who were selected by random sampling. Data analysis used the Wilcoxon test, T-Dependent, Mann-Whitney and T-Independent tests. The results showed an effect of providing education using e-poster media on knowledge, attitudes and behavior (p 0.05).